(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The possibility of utilizing groundwater as a source of water supply for public use is always attractive This research was focused to evaluate the groundwater potential of Kazaure area, Nigeria. The methodology adopted were mainly primary data in which six different thematic maps were integrated to generate the groundwater potential model (GWPM. It was produced by Weighted Linear Combination (WLC) where each class individual’s weight was multiplied by the map scores. In the research, Erdas Imagine 9.2, PCI Geomatica 10.0, ArcMap 9.3 and Expert Choice 10.0 in a GIS environment were used. Vertical electrical sounding (VES) was conducted using Ohmega resistivity meter with Schlumberger configuration. IP12win software was used in plotting the curves which revealed the resistivity, layers and thickness of the VES stations. Geological mapping was carried out using topographical map on a scale of 1:50,000Measurement of the depth to groundwater table in hand dug wells was carried out using dip meter. Water samples were collected and analyzed. Atomic Absorption Spectrometry (AAS) and X-Ray Fluorescence (XRF) were used in the analysis of water quality at the Multi-user laboratory, Chemistry Department, Ahmadu Bello University Zaria, Nigeria.